Varied orbital manifestations of paranasal sinus disease - Harugop, Anil Kumar S.; Mudhol, Ramesh S.; Bhimanapati, Deepthi; Soni, Samanvaya; Bellad, Shama A.; Achuta, Aparna; ., Suhasini (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Even though sinusitis is a common clinical entity, its complications are seen rarely after the advent of antibiotics. Hence we aimed to analyse varied clinical presentations and manifestations of orbital involvement in paranasal sinus diseases and their outcome. Methods: Hospital based prospective study done from January 2007 to December 2017. We selected 65 patients in our study based on our inclusion and exclusion criteria. Type of orbital involvement was analysed by computed tomography scan. Immediate aggressive medical management was started and surgery was undertaken if there is no clinical improvement in 48 hours. Endoscopic sinus surgery done along with orbital decompression and drained pus was sent for culture sensitivity. Patients were followed up regularly and suction clearance was done. Results: Out of 65 patients, 50 were male and 15 were female. 24 patients had bacterial pathology, 40 had fungal pathology and 1 patient had non specific inflammatory disease consistent with mucocoele. Out of 24 bacterial sinusitis, 2 had bilateral disease and 1 patient had scalp and neck extension. Out of 40 fungal sinusitis, 2 patients had 6th cranial nerve palsy with sphenoid disease, 5 patients had palatal extension and 8 patients had intracranial involvement. Conclusions: All cases of orbital oedema and proptosis should be thoroughly evaluated for sinus disease. Computed tomography aids to know the extent of disease, deciding about the type and mode of intervention. Early diagnosis and immediate intervention reduces significant mortality and morbidity. However regular follow up, counselling the patients and relatives helps in achieving appropriate outcome.